Directed Forgetting of Happy and Angry Faces: The Effects of Facial Emotion and Sex on Recognition Memory for Facial Identity - TAY, Kay Chai (Institutional Knowledge at Singapore Management University, 2014)
The literature on directed forgetting – which refers to forgetting the specified information intentionally – has almost exclusively focused on either emotional words or pictures. Consequently, little is known about the impact of facial stimuli that demand more complex cognitive processing than words or pictures. A pilot study was conducted to obtain norm ratings on 152 facial images portraying neutral, happy and angry emotions. From this set of facial stimuli, 96 faces were selected for the main study. In the main study, 75 female participants were presented with 48 faces individually with equal number of happy and angry and, male and female faces. Half the faces were followed by a cue to remember and the remaining half a cue to forget. Following which, all participants were presented with emotionally neutral faces and asked to indicate if they had seen the face or not, including those they were previously told to forget. Results demonstrated that directed forgetting effects were significantly modulated by facial emotions and sex of faces. Specifically, forgetting costs (i.e., impaired memory for to-be-forgotten faces) were eliminated for angry faces and male faces. Given the literature that has documented happy face advantages in remembering (e.g., D'Argembeau, Van der Linden, Comblain, & Etienne, 2003), our findings suggest that forgetting of emotional faces may implicate potentially different mechanisms from those underlying remembering. The findings also imply the important role of emotional 3 expressions and sex of faces for adaptive memory: Among women, memory is enhanced for male angry faces because they signal threat or danger (Becker, Kenrick, Neuberg, Blackwell, & Smith, 2007) and for female happy faces because they are associated with the notion of “tending and befriending” (Taylor et al., 2000).